Trends and correlates of overweight/obesity in Czech adolescents in relation to family socioeconomic status over a 12-year study period (2002-2014) - Erik Sigmund; Petr Badura; Dagmar Sigmundová; Jaroslava Voráčová; Jiří Zacpal; Michal Kalman; Jan Pavelka; Jana Vokacová; Vladimír Jr Hobza; Zdenek Hamrik (BMC, 2018)
Abstract Background This study examined a) trends in overweight/obesity, moderate-to-vigorous physical activity (MVPA), and screen time (ST) among Czech adolescents over a 12-year study period (2002-2014) in relation to family affluence (FA) and b) correlates of adolescent overweight/obesity from different FA categories. Methods A nationally representative sample of 18,250 adolescents (51.4% girls) aged 10.5-16.5 years was drawn from the Czech Health Behaviour in School-aged Children questionnaire-based surveys in 2002, 2006, 2010, and 2014. Using the FA scale, the socioeconomic status (SES) of the respondents' families was assessed. SES-stratified trends in the prevalence of overweight/obesity meeting the MVPA (≥60 min/day), and ST (≤2 h/day) recommendations were assessed using logistic regression. Results A trend-related significant increase (p < 0.05) in the prevalence of overweight/obesity was observed in low−/medium-FA boys and medium−/high-FA girls. Unlike in high-FA adolescents, a significant decrease was revealed in the rates of meeting the MVPA recommendation in low-FA boys (28.9%2002 → 23.3%2014, OR = 0.75, 95% CI = 0.59-0.95, p < 0.05) and girls (22.3%2002 → 17.3%2014, OR = 0.73, 95% CI = 0.57-0.92, p < 0.01). A significant (p < 0.001) trend-related increase in excessive ST was evident in adolescents regardless of gender and FA category. Generally, girls and older adolescents had lower odds of overweight/obesity than boys and 11-year-old adolescents. While in the high-FA category of adolescents, achieving 60 min of MVPA daily and the absence of excessive ST on weekdays significantly (p < 0.01) reduced their odds of being overweight/obese, in low-FA adolescents this was not the case. Conclusions High rates of overweight/obesity and a poor level of daily MVPA among low-FA children provide disturbing evidence highlighting the necessity of public health efforts to implement obesity reduction interventions for this disadvantaged population.